Genetic and shell-shape analyses of Orlitia borneensis (Testudines: Geoemydidae) reveal limited divergence among founders of the European zoo population - Palupčíková, Klára; Somerová, Barbora; Protiva, Tomáš; Rehák, Ivan; Velenský, Petr; Hulva, Pavel; Gunalen, Danny; Frynta, Daniel (Zootaxa, 2012)
The Malaysian Giant Turtle (Orlitia borneensis) is a poorly known turtle with rapidly decreasing numbers in nature in spite of its strong protection on paper. Most individuals of this species kept in European zoos and included in captive breeding programs are confiscates from the illegal trade for food consumption and their geographic provenance is unknown. This study was aimed to assess genetic and phenotypic variation of the founders of this captive population. We sequenced the mitochondrial cytochrome b gene and found 23 haplotypes. We constructed a haplotype network and examined demographic changes by Bayesian skyline plots of the effective population size. The maximum sequence divergence was less than 1.5% and the phylogenetic structure of the haplotypes was supported poorly. A close genetic similarity among sampled turtles was further confirmed by sequencing the nuclear R35 gene, while the geometric morphometrics of the shell-shape were likewise similar. Thus, the examined captive population of O. borneensis may be further treated as a single conservation unit.